Pediatric health care use during the COVID‐19 pandemic: Lessons learned from the initial 2020 wave - Anju Wagh; Sharon Pan; Stephen Gordon; Lenka Hellerova; Yeqing Ji; Henry Park; Shiu‐Lin Tsai (Journal of the American College of Emergency Physicians Open)
Abstract Objective During the height of the coronavirus disease‐2019 (COVID‐19) pandemic, there was a decline and shift in pediatric medical care use. We aimed to assess changes to pediatric medical use and perceptions/barriers that influenced caregivers’ decision‐making during the New York State mandated lockdown from March 22 to June 8, 2020, in a population that opted to use the pediatric emergency department (PED) during this period. This study was conducted in New York City (NYC), one of the epicenters at the height of the COVID‐19 pandemic. Methods From June 14 to December 28, 2020, a convenience sample of caregivers who brought children 0–17 years to a NYC PED completed a survey. Results Participants in the survey included 290 caregivers: 76% were Hispanic; 91% reported having accessed medical care when their children were ill during the lockdown. In‐person primary care visits decreased from 64% before to 9% during lockdown; 28% missed well‐child checkups or vaccinations, and 26% missed specialist appointments. Telemedicine usage increased from 10% to 54%; none reported lack of internet or electronic devices as barriers to using telemedicine. Regarding access to care: 36% perceived increased difficulty during the lockdown, whereas 56% felt no difference. Barriers included fear of contracting COVID‐19 and government advice to avoid health care visits for minor problems. Conclusion During the initial wave of the COVID‐19 pandemic, medical care shifted from an in‐person to a virtual platform. Identification of factors and barriers surrounding caregivers’ decision‐making may positively inform strategies toward future public health emergencies.